2013
DOI: 10.1038/mt.2013.183
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Bacteria for the Visualization of Targeted Delivery of a Cytolytic Anticancer Agent

Abstract: A number of recent reports have demonstrated that attenuated Salmonella typhimurium are capable of targeting both primary and metastatic tumors. The use of bacteria as a vehicle for the delivery of anticancer drugs requires a mechanism that precisely regulates and visualizes gene expression to ensure the appropriate timing and location of drug production. To integrate these functions into bacteria, we used a repressor-regulated tetracycline efflux system, in which the expression of a therapeutic gene and an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(129 citation statements)
references
References 48 publications
2
127
0
Order By: Relevance
“…Jiang et al inserted Renilla luciferase and ClyA genes on both sides of this promoter to simultaneously visualize the bacteria and deliver the toxin gene [30].…”
Section: Controllable Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jiang et al inserted Renilla luciferase and ClyA genes on both sides of this promoter to simultaneously visualize the bacteria and deliver the toxin gene [30].…”
Section: Controllable Gene Expressionmentioning
confidence: 99%
“…The most common way to image bacteria in small animal models is labeling them with luminenescence gene operon derived from a luminescent bacterial strain [6,7,30]. The bacterial luciferase (lux) operon encodes five gene clusters, lux C, D, A, B, and E. Lux A and B express bacterial luciferase enzyme, while lux C, D, and E control fatty aldehyde enzyme complex production, which synthesizes the substrates.…”
Section: In Vivo Monitoring Of Bacteria With Molecular Imaging Technomentioning
confidence: 99%
See 1 more Smart Citation
“…Several strains of S. Typhimurium have been constructed for the purpose of tumor targeting and chemotherapy delivery, most mentionable being: A1 (Zhao et al, 2005)/A1-R Hiroshima et al, 2013;Hoffman, 2016;Hiroshima et al, 2014;Yano et al, 2014;Murakami et al, 2016;Kawaguchi et al, 2016), BRD509/BRD509E (Yoon et al, 2014;al-Ramadi et al, 2009), χ4550 (Saltzman et al, 1996), CRC2631 (Eisenstark et al, 2007), ΔppGpp (Jiang et al, 2013;Kim et al, 2015;Nguyen et al, 2010), LH340 (Zhang et al, 2007;VanCott et al, 1998;Jia et al, 2012), LVR01 (Grille et al, 2014), MvP728 (Manuel et al, 2011;Xu et al, 2014;Xiong et al, 2010), RE88 (Xiang et al, 2005;Lee et al, 2006;Qian et al, 2011), SA186 (Chirullo et al, 2015), SB824 (Roider et al, 2011), SL3261 (Lin et al, 2012;Ye et al, 2013), SL7207 (Jarosz et al, 2013;Li et al, 2013;Shi et al, 2016;Berger et al, 2013), YB1 (Li et al, 2017;Yu et al, 2015), and VNP20009 . VNP20009 was created by Low et al ) from strain 14028s through selection for hyperinvasion by chemical/UV mutagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Three methods are commonly used to treat cervical cancer: surgery, chemotherapy and radiation therapy. However, recent research has demonstrated that engineered bacteria can be used to treat cancer [4], and the development of a new treatment method for cervical cancer is feasible.…”
Section: Introductionmentioning
confidence: 99%